Synthesis, in silico and Pharmacological Evaluation of New Thiazolidine-4-Carboxylic Acid Derivatives Against Ethanol-Induced Neurodegeneration and Memory Impairment [Retraction] - Naz S; Al Kury LT; Nadeem H; Shah FA; Ullah A; Paracha RZ; Imran M; Li S (Dove Medical Press, 2022)
Naz S, Al Kury LT, Nadeem H, et al. J Inflamm Res. 2022;15:3643–3660. The Editor and Publisher of the Journal of Inflammation Research wish to retract the published article. Concerns were raised regarding the alleged duplication of images in Figure 4 and Figure 6 with similar images from Ullah et al, 2022 (https://doi.org/10.2147/JIR.S351913). Specifically, Figure 4E, Hippocampus, P9, appears to have been duplicated with the same image from Figure 8E, Hippocampus, Ethanol + DNP from Ullah et al, 2022 (https://doi.org/10.2147/JIR.S351913). Figure 4E, Hippocampus, Saline appears to have been duplicated with the same image from Figure 4E, Hippocampus, Ethanol. Figure 6B, TNF-α, Hippocampus, P8, appears to have been duplicated with the same image from Figure 10D, TNF-α, Hippocampus, Ethanol + Cb from Ullah et al, 2022 (https://doi.org/10.2147/JIR.S351913). Figure 6C, p-NF-κB, Hippocampus, P8, appears to have been duplicated with the same image from Figure 10F, COX-2, Hippocampus, Ethanol + DNP from Ullah et al, 2022 (https://doi.org/10.2147/JIR.S351913). Figure 6C, p-NF-κB, Hippocampus, P8, appears to have been duplicated with the same image from Figure 6C, p-NF-κB, Hippocampus, P9. The authors responded to our queries but were unable to provide a satisfactory explanation for the duplicated images. The Editor requested for the article to be retracted and the authors were notified of this. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.